Optical bistability in shape-memory nanowire metamaterial array - Nagasaki, Yusuke (2019)
Non-volatile temperature-induced structural phase transitions such as those found in chalcogenide glasses are known to lead to strong changes in optical properties and are widely used in rewritable optical disk technology. Herein, we demonstrate that thermally activated optical memory can be achieved via the nanostructural reconfiguration of a metallic nanowire metamaterial array made from a shape-memory alloy: A nickel-titanium film of nanoscale thickness structured on the subwavelength scale exhibits bistability of its optical properties upon temperature cycling between 30 °C and 210 °C. The structure, comprising an array of NiTi nanowires coated with a thin film of gold to enhance its plasmonic properties, can exist in two non-volatile states presenting an optical reflectivity differential of 12% via nanoscale mutual displacements of alternating nanowires in the structure. Such all-metal shape-memory photonic gratings and metamaterials may find applications in bistable optical devices.